(untitled) (International journal of medical sciences, 2025)
A previous stroke is a major factor in the development of cognitive impairment. Cognitive dysfunctions are among the earliest manifestations of disturbances in the nervous system. In clinical practice, various psychophysiological tests and their combinations are used. This article presents the results of applying the MMSE and MoCA scales. The study included 53 patients (23 women and 30 men) aged 55 to 75 years.